2004
DOI: 10.1007/s00535-003-1285-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of antimitochondrial antibody in Japanese corporate workers in Kanagawa prefecture

Abstract: AMA is not a rare antibody in the general population, but few people develop recognizable PBC even if they have AMA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
31
2
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 22 publications
4
31
2
1
Order By: Relevance
“…Considering both PBC and AMA prevalences in the Japanese population, Shibata et al inferred that only 0.73% of the AMA carriers in Japan should suffer from symptomatic PBC. (23) These data, which are in keeping with ours, point out that AMArelated conditions are a wide, poorly known area from which PBC, as the tip of the iceberg, would just be the known side.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Considering both PBC and AMA prevalences in the Japanese population, Shibata et al inferred that only 0.73% of the AMA carriers in Japan should suffer from symptomatic PBC. (23) These data, which are in keeping with ours, point out that AMArelated conditions are a wide, poorly known area from which PBC, as the tip of the iceberg, would just be the known side.…”
Section: Discussionsupporting
confidence: 85%
“…(17)(18)(19) Systematic screening of blood donors and healthy subjects shows AMA-positive results in 0.07%-9.9% of individuals, depending on the techniques and diagnostic thresholds used, as well as on the type, age, and sex structures of the populations screened. (20)(21)(22)(23)(24) The relatively high rate (2.5% of all tests) of AMA positivity observed in our study may be related to the equivocal nature of low titers of AMAs detected by IF, but is more likely to be driven by the population concerned. The proportion of positive results is typically bigger in the female population above 40 years.…”
Section: Discussionmentioning
confidence: 69%
“…Others have reported the prevalence of AMAs in normal populations to be as high as 0.6%. 28,29 Nevertheless, these studies did not assess the prevalence of AMAs in healthy controls matched for age and sex to a cohort of PBC patients. In another study, the prevalence of AMAs among corporate workers undergoing annual health check-ups was 0.44% (5 out of 1145); however, when the data were stratified by sex, the AMA prevalence in females was 0.91%, and all 5 of the affected individuals were females older than 40 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…However, the AMA-positive rate of healthy people in Japan was 0.64% (11/1714) (12). In addition, enzyme-linked immunosorbent assay (ELISA)/ western blot tests indicated that 4.6% (14/302) of the entire spectrum of collagen diseases and 4.2% (3/71) of SLE cases were AMA-positive, while the total AMA-positive rate of collagen diseases (excluding cases diagnosed as PBC) was 3.0% (9/297) (13).…”
Section: Discussionmentioning
confidence: 99%